Synthesis of single-walled carbon nanotubes by the pyrolysis of a compression activated iron(II) phthalocyanine/phthalocyanine metal-free derivative/ferric acetate mixture - Mugadza, Tawanda; Antunes, Edith; Nyokong, Tebello (Indian Academy of Sciences, 2016)
This paper reports on the synthesis of single walled carbon nanotubes (SWCNTs) from an activated mixture of iron (II) phthalocyanine, its metal-free derivative and ferric acetate. The powdered mixture was activated by compression into a tablet by applying a force of 300 kN, followed by re-grinding into powder and heating it to high temperatures (1000°C). The activation by compression resulted in more than 50% debundling of SWCNTs as judged by transition electron microscopy. Acid functionalization of the SWCNTs was confirmed by the increase in the D:G ratio from 0.56 to 0.87 in the Raman spectra and the observation of an average of one carboxylic acid group per 13 carbon atoms from thermogravimetric analysis (TGA). TGA also showed that the initial decomposition temperatures for the activated and non-activated mixtures to be 205°C and 245°C, respectively. Hence, activation leads to the lowering of the pyrolysis temperature of the phthalocyanines. X-ray diffraction, electronic absorption and Fourier transform infrared spectra were also employed to characterize the SWCNT